Using RNA-Seq to Investigate Immune-Metabolism Features in Immunocompromised Patients With Sepsis - Cheng, Po-Liang; Chen, Hsin-Hua; Jiang, Yu-Han; Hsiao, Tzu-Hung; Wang, Chen-Yu; Wu, Chieh-Liang; Ko, Tai-Ming; Chao, Wen-Cheng (Frontiers in Medicine, 2021)
Objective: Sepsis is life-threatening and leads to complex inflammation in patients with immunocompromised conditions, including cancer and receiving immunosuppressants for autoimmune diseases and organ transplant recipients. Increasing evidence have shown that RNA-Sequencing (RNA-Seq) can be used to define subendotype in patients with sepsis; therefore, we aim to use RNA-Seq to identify transcriptomic features among immunocompromised patients with sepsis Methods: We enrolled patients who were admitted to medical intensive care units (ICUs) for sepsis at a tertiary referral centre in central Taiwan. Whole blood on day-1 and day-8 were obtained for RNA-Seq. We used Gene Set Enrichment Analysis (GSEA) to identify the enriched pathway of day-8/day-1 differentially expressed genes and MiXCR to determine the diversity of T cell repertoire. Results: A total of 18 immunocompromised subjects with sepsis and 18 sequential organ failure assessment (SOFA) score-matched immunocompetent control subjects were enrolled. The ventilator-day, ICU-stay and hospital-day were similar between the two groups, whereas the hospital mortality was higher in immunocompromised patients than those in immunocompetent patients (50.0% vs 5.6%, p<0.01). We found that the top day-8/day-1 up-regulated genes in the immunocompetent group were mainly innate immunity and inflammation relevant genes, including PRSS33, HDC, ALOX15, FCER1A and OLR1, whereas a blunted day-8/day-1 dynamic transcriptome was found among immunocompromised septic patients. Functional pathway analyses of day-8/day-1 differentially expressed genes identified the up-regulated functional biogenesis and T cell-associated pathways in immunocompetent patients recovered from sepsis, whereas merely down-regulated metabolism-associated pathways were found in immunocompromised septic patients. Moreover, we used MiXCR to identify a higher diversity of TCR in immunocompetent patients both on day-1 and day-8 than those in immunocompromised patients. Conclusions: Using RNA-Seq, we found compromised T cell function, altered metabolic signalling and decreased T cell diversity among immunocompromised septic patients, and more mechanistic studies are warranted to elucidate the underlying mechanism.